2018
DOI: 10.4103/gmit.gmit_12_18
|View full text |Cite
|
Sign up to set email alerts
|

Size, type, and location of myoma as predictors for successful laparoscopic myomectomy: A Tertiary Government Hospital experience

Abstract: Background:Laparoscopic myomectomy (LM) is a preferred alternative to abdominal myomectomy due to shorter hospitalization, faster recovery, and decreased intraoperative adhesions. The criteria, however, which constitute proper selection of patients for LM, are still a matter of debate. Since conversion to either laparoscopic-assisted myomectomy (LAM) or laparotomy (EL) entails longer time and increased costs compared to performing an open procedure from the outset, this research aims to evaluate size, location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…Although there are no universally accepted selection criteria for the surgical approach, based on our results, women with 3 or more fibroids and whose largest myoma is ≤9 cm can be successfully treated through laparoscopy. Our results agree with those of previous studies that showed that the number of complications, surgical difficulties and risk of laparoconversion increase if LM is performed in patients with these characteristics ( 11 , 20 22 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although there are no universally accepted selection criteria for the surgical approach, based on our results, women with 3 or more fibroids and whose largest myoma is ≤9 cm can be successfully treated through laparoscopy. Our results agree with those of previous studies that showed that the number of complications, surgical difficulties and risk of laparoconversion increase if LM is performed in patients with these characteristics ( 11 , 20 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…The association between the surgeon's experience and the laparoscopic approach was statistically significant ( p < 0.001), with 92% of the laparoscopies performed by expert surgeons and 66% performed by training surgeons. The surgeon's experience continues to be decisive for successful LM ( 20 , 21 ). We therefore found no association between the type of myoma and the surgical approach ( p = 0.767), given the expert surgeon's skill in managing different types of myomas.…”
Section: Discussionmentioning
confidence: 99%
“…Among different types of uterine myoma, intramural and subserous myomas were associated with a higher successful rate. [ 2 ] Ulipristal acetate has been introduced as preoperative treatment of patients with large fibroids; however, studies showed that it results in a more technically difficult situation with the potential risk of incomplete resection due to anatomical distortion and unclear cleavage planes. [ 3 ] Although minimally invasive surgery represents the gold standard treatment, laparoscopic myomectomy still requires adequate knowledge of the risk factors for complications, of which the most common is bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Subserosal leiomyomas are located outside the uterus, and the shallow defect in the uterus caused by enucleation of the subserosal leiomyoma can be adequately sutured and repaired. 41 In patients with intramural leiomyomas, however, especially large leiomyomas that have penetrated through the entire myometrium, suturing the deep and total layers of the myometrium may be difficult, resulting in inadequate uterine repair. 42 This may increase the amount of blood that oozes from the surgical incision, and a hematoma may form, leading to a higher perioperative HBL than in subserosal leiomyoma enucleation.…”
Section: Discussionmentioning
confidence: 99%